DEVELOPMENT OF THE LEARNING TOOLS OF BIOLOGY TEACHING MATERIAL WASTE MANAGEMENT ORIENTED ENTREPRENEURSHIP - ., Prasetiyo; ., Sumarno (BIOMA, 2011)
ABSTRACT Waste management material on the subjects of biology can be used to enhance the values ââof entrepreneurship for students. Therefore, we need to develop relevant learning tools. The purpose of this research is to develop entrepreneurship-oriented learning tool which is effective to increase the values ââof students entrepreneurship. The study was conducted in SMA 11 Semarang (Semarang 11 th high school) with the subject of tenth grade students of the 2010/2011 school year. The type of research is the research and development (R & D). This research is used to produce certain products, as well as test the effectiveness of these products. Product to be produced is the learning tools of biology that include: instructional materials, lesson plans, syllabi and worksheets. The result showed that the resulting product has validity value of (Va.) = 4. The average score for syllabi, lesson plans, teaching materials and worksheets is = 4. In addition, the entrepreneurship learning interest of students in entrepreneurship-oriented waste management learning have increased 8.2% for ordinary regular classes and 6.4% for the excellent class. The conclusion is, the entrepreneurial-oriented learning tool developed is effective way to increase entrepreneurship interest in learning biology. Key words: waste, entrepreneurship, learning tools